2021
DOI: 10.1139/cjas-2019-0188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary red-osier dogwood (Cornus stolonifera) on growth performance, blood profile, ileal morphology, and oxidative status in weaned pigs challenged with Escherichia coli K88+

Abstract: Twenty-eight piglets weaned at 21 days of age (6.94 ± 0.28 kg of body weight) were assigned to one of four dietary treatments for 14 days: 1) negative control (NC; a corn-wheat-soybean meal-based diet), 2) positive control (PC; NC + 0.025% antimicrobial growth promoter [AGP]), 3) ROD2 (2% red-osier dogwood [ROD]), and 4) ROD4 (4% ROD). All pigs were orally inoculated with Escherichia coli K88+ on day 8. The pre-planned orthogonal test was performed to compare 1) NC vs. PC and 2) NC vs. ROD. The inclusion of RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
6
1
Order By: Relevance
“…The inclusion of polyphenols in diet at 0.4% in this study appears safe, as no change in body weight was documented throughout the two-week dietary intervention. This is in accordance with previous studies that show that similar amounts of phytochemicals in diets do not negatively impact growth, and may even improve it (12,16). Despite being quite different with regards to phenolic compound composition, the PA and DW diets both led to increased fecal mucin, suggesting that flavan-3-ol condense tannins from peas, beans or fruit are not unique in their ability to increase fecal mucin (12,30,31).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The inclusion of polyphenols in diet at 0.4% in this study appears safe, as no change in body weight was documented throughout the two-week dietary intervention. This is in accordance with previous studies that show that similar amounts of phytochemicals in diets do not negatively impact growth, and may even improve it (12,16). Despite being quite different with regards to phenolic compound composition, the PA and DW diets both led to increased fecal mucin, suggesting that flavan-3-ol condense tannins from peas, beans or fruit are not unique in their ability to increase fecal mucin (12,30,31).…”
Section: Discussionsupporting
confidence: 93%
“…A study in pigs with a lower inclusion rate of 0.5% ROD extract showed no effect on ileal microbial alpha diversity (Shannon and Simpson) but a prebiotic effect on Lactobacillus species was noted along with no change to growth performance (33). A study in weaned pigs challenged with Escherichia coli k88+ found that 2% and 4% ROD extract diets conferred beneficial effects on growth performance; however, microbial composition was not assessed (16). Phylogenetic diversity in the DW group was maintained at day 14, which could be explained by the increased abundance of Akkermansia municiphila , Parasutterella and Turicibacter, which only appeared in this DW group at day 14 and were not detected in any group at day 0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the antibiotic and control treatments, dietary supplementation of ROD extract did not influence the serum TAP and SOD of broiler chickens challenged or unchallenged with SE -LPS. Antimicrobial growth promoters have been used to improve antioxidant status of weaned pigs ( Koo et al., 2020 ). The result obtained in the current study suggests that supplementation of ROD extract maintained TAP and SOD in the same capacity of antibiotics.…”
Section: Discussionmentioning
confidence: 99%